Linezolid for treatment of ventriculoperitoneal shunt meningitis caused by Methicillin resistant Staphylococcus aureus not responding to Vancomycin. - Keyal, Niraj Kumar; Nepal, Pankaj Raj; Tamrakar, Karuna (Journal of Nepalese Society of Critical Care Medicine, 2024)
Methicillin resistant Staphylococcus aureus is a common cause of ventriculoperitoneal shunt meningitis. It carries high morbidity and mortality. We present a case of 8-year male who presented with extradural hematoma secondary to trauma. The patient underwent craniotomy and evacuation of hematoma. Ventriculoperitoneal shunt was placed for hydrocephalus and was discharged home. After one month, he developed fever, abdominal pain and altered sensorium and was diagnosed as pyogenic meningitis secondary to Methicillin resistant Staphylococcus aureus. Patient was treated with Vancomycin and Meropenem and the shunt was exteriorized, but there was no clinical improvement over next three days. Linezolid was initiated. After two days, there was improvement in fever and headache. The distal end of shunt was removed. After 21 days of medical and surgical management of meningitis and hydrocephalus, patient was discharged home. Linezolid may be helpful as a second line treatment of Methicillin resistant Staphylococcus aureus associated ventriculoperitoneal shunt meningitis in patients who fail to respond to Vancomycin.